Kereeen...!!! cerita seru dan fakta sains menakjubkan / Rauhiyatul Jannah; penyunting, Tin Zulaeha, Anggita Linggar; ilustrator, Hendra Aditya - RAUHIYATUL JANNAH; Tin Zulaeha; Anggita Linggar; Hendra Aditya (Visi Mandiri, 2016)
104 hlm. : ilus. ; 24 cm.